Research on hardware Trojan defense - Kan WANG; Hao CHEN; Xu-guang GUAN; Yong GU (网络与信息安全学报)
The definition and features of hardware Trojan were described firstly.After that,recent researches of defense and detection techniques were categorized with complete comparison and analysis.Then,current researches limitations were discussed based on the concepts and the trends perspectives of hardware Trojan defense and detection were proposed.